On the Current Debate on the Clinical Method - Alfredo Darío Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
At present, a debate has raised on the clinical method as priority policy in health services. Internists are at the forefront of these discussions. The clinical method is a variant of the scientific method applied to the medical assistance of a single individual. It is aimed at the obtention of the most accurate diagnosis, the elaboration of a prognosis and the materialization of action. The conceptualization of the clinical method that prevails among Cuban internists, results from the National School of Clinic, where internists have played a key role during the last 50 years. Their task now is to continue to preserve and transmit this treasure that the essence of clinics is, in an unstable and changing setting. Other clinicians can also join this effort. In this paper, a number of actions are proposed to achieve these purposes.